Confined and unreinforced masonry structures in seismic areas: Validation of macro models and cost analysis. (15th November 2019) - Ahmed, Asfandyar; Shahzada, Khan; Ali, Syed Muhammad; Khan, Akhter Naeem; Shah, Syed Azmat Ali
Highlights: A validation of tools for seismic assessment of URM and CM buildings is made against full-scale tests. Good prediction of the response in deformation and damage is obtained by using pushover analysis. An assessment of response factors is made for the URM and CM solutions of the house. URM and CM allow a cost saving of the structure respectively of 28% and 20% as compared to RC. Abstract: Modern structural design requires consideration of sustainability parts from a life cycle perception, but also the initial design phase in which seismic actions have a substantial influence on the design of the structure. In recent times, the seismic assessment of masonry buildings by means of macro-element modeling methodologies has become popular, by application of performance-based evaluation techniques using nonlinear lateral load procedures (Pushover). This study addresses the endorsement of these methodologies by referring to two full-scale brick masonry structures subjected to a lateral loading conditions. The lateral load response of tested unreinforced masonry (URM) and confined masonry (CM) structures is compared with the response of the numerical models. The considered numerical models have good agreement for satisfactorily predicting the response of the experimental test and hence are capable of being used in a performance-based evaluation. Then, pointing to the characteristic housing of northern Pakistan and its typical design with a reinforced concrete (RC) building, the validated numerical models are used to estimate the hazard-resistant potentials of the URM and CM options for one, two and three story options, particularly in relation with maximum lateral load capacity. The load deformation response of both the typologies was also compared for the mentioned three story levels. It was observed that by confining the masonry its ductility capacity increases considerably, hence making it more suitable to be used in earthquake prone regions. Masonry structures are also compared regarding the construction costs compared to the RC typology. With regard to the dwellings studied, the projected lateral load behavior for masonry structures indicate the ability to withstand lateral loads adequately. These structures also allow a significant reduction in costs (up to 28%) compared to RC, hence appearing as challenging alternatives.